Influence of pH on short-cut denitrifying phosphorus removal - Wei Li (Water Science and Engineering, 2018)
Through a series of experiments using denitrifying phosphorus-accumulating sludge in sequencing batch reactors (SBRs), the variations of the intracellular polymers during the anaerobic phosphorus release process at different pH values were compared, the probable reasons for different performances of phosphorus removal were examined, and system operations in a typical cycle were investigated. The results show that the phosphorus removal rate was positively correlated with pH values in a range of 6.5–8.5. When the pH value was 8.0, the anaerobic phosphorus release rate and anoxic phosphorus uptake rate of the activated sludge were 20.95 mg/(g∙h) and 23.29 mg/(g∙h), respectively; the mass fraction of poly-β-hydroxybutyrate (PHB) increased to 62.87 mg/g under anaerobic conditions; the mass fraction of polyphosphate was 92.67 mg/g under anoxic conditions; and the effluent concentration of total phosphorus (TP) was 1.47 mg/L. With the increase of pH, the mass fraction of acetic acid and PHB also increased, and the absorption rate of acetic acid was equal to the disintegration rate of polyphosphate. When the pH value was above 8.0, biological phosphorus removal was achieved by chemical phosphorus precipitation, and the phosphorus removal rate decreased. Keywords: Denitrifying phosphorus removal, pH, Removal rate, PHB